Comparative Anatomical Study on the Isthmus of Pati and Chara-Chemballi Ducks (Anas platyrhynchos domesticus) during Laying Periods - Deka, Anil; Baishya, G.; Sarma, Kabita; Dev Choudhry, K. B.; Rajkhowa, J. (Indian Journal of Veterinary Anatomy, 2015)
Grossly, the isthmus was short and narrow in comparison to magnum and was situated ventral to the caudal lobe of the left kidney. Histologically, the tunica mucosa of isthmus of both Pati and Chara-Chemballi ducks were having primary, secondary and tertiary folds. It was lined by simple ciliated columnar epithelium with goblet cells in both ducks. Histochemically, the surface epithelium and glandular layers of isthmus showed intense PAS reaction in Chara-Chemballi duck than Pati duck.